الهوية الثقافية الجزائرية في زمن العولمة الثقافية - التحديات وسبل المواجهة - - الفتني, صديقة; مالكي, حنان (University of Eloued جامعة الوادي, 2021)
نهدف من خلال هذا المقال إلى إبراز التأثيرات والإنعكاسات التي تخلفها موجة العولمة الثقافية على الهوية الثقافية الجزائرية، إضافة إلى تحديد أهم الآليات والأساليب التي بإمكان المجتمع الجزائري أن يعتمدها في مواجهة شبح العولمة الثقافية، خاصة وأن هذه الأخيرة تمارس ضغوطا وإكراهات على المجتمع الجزائري، ما جعلته مغتربا بين متطلبات الأصالة وتأثيرات العولمة. في سبيل تحقيق أهدافنا قسمنا العمل إلى ثلاث مباحث، المبحث الأول: تمحور حول الهوية الثقافية الجزائرية وأبرز مكوناتها، لنعرج لموضوع العولمة الثقافية وأهم وسائلها بالمبحث الثاني، وتناولنا في مبحث ثالث إنعكاسات العولمة الثقافية على الهوية الثقافية الجزائرية من جهة، وعرض أهم الآليات التي يمكن إعتمادها لمواجهة شبح العولمة من جهة أخرى، وخلص هذا العمل إلى أن العولمة الثقافية خلفت تأثيرات سلبية على مختلف مكونات الهوية الثقافية الجزائرية، كما خلص أيضا إلى ضرورة تفعيل دور كل مؤسسات المجتمع المدني في سبيل حماية الهوية الثقافية الجزائرية من خطر العولمة الثقافية. Through this article, we aim to highlight the effects and repercussions that the wave of cultural globalization has on the Algerian cultural identity, in addition to identifying the most important mechanisms and methods that Algerian society can adopt in facing the specter of cultural globalization, especially since the latter exerts pressures and coercions on Algerian society, which made it An alienation between the requirements of originality and the effects of globalization. In order to achieve our goals, we divided the work into three topics, the first topic: centered on the Algerian cultural identity and its most prominent components. Let us turn to the topic of cultural globalization and its most important means in the second topic, and in the third topic we dealt with the implications of cultural globalization on the Algerian cultural identity on the one hand, and present the most important mechanisms that can be adopted. To face the specter of globalization on the other hand, this work concluded that cultural globalization has had negative effects on the various components of the Algerian cultural identity. It also concluded that the role of all civil society institutions should be activated in order to protect the Algerian cultural identity from the threat of cultural globalization.
مجلد12، عدد1
Keywords: الهوية الجزائرية ; الثقافة المحلية ; الذات الثقافية ; العولمة ; المجتمع المدني; Algerian Identity ; Local Culture ; The Cultural Self ; Globalization ; Civil Society